The incidence of congenital malformations in children born in consequence of assisted reproductive technologies taking into account medical history - Stoeva, T. U.; Sinenko, V. V.; Sitnik, V. V. (Journal of Education, Health and Sport, 2016)
Stoeva T. U., Sinenko V. V., Sitnik V. V. The incidence of congenital malformations in children born in consequence of assisted reproductive technologies taking into account medical history. Journal of Education, Health and Sport. 2017;7(1):460-467. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.321396 http://ojs.ukw.edu.pl/index.php/johs/article/view/4282 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2017; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.01.2017. Revised 16.01.2017. Accepted: 24.01.2017. THE INCIDENCE OF CONGENITAL MALFORMATIONS IN CHILDREN BORN IN CONSEQUENCE OF ASSISTED REPRODUCTIVE TECHNOLOGIES TAKING INTO ACCOUNT MEDICAL HISTORY T. U. Stoeva, V. V. Sinenko, V. V. Sitnik Odessa National Medical University, Ukraine tendov@rambler.ru Abstract Assisted reproductive technologies (ART) become more and more popular. The objective: to determine the frequency and structure of congenital malformations in children born as a result of application of ART (ICSI) with taking into consideration anamnestic factors. Materials and methods: 74 children born after ART (ICSI) aged 1 month - 7 y. o. were examined. The presence of CM is confirmed by the data of laboratory and instrumental investigations. Along with clinical examination of the children the analysis of the antenatal and perinatal period was carried out, particular attention was paid to the study of the preconceptual stage peculiarities. The results and discussion: In the structure of CM those of cardiovascular system predominated with the share of (72.2 ± 10.5)%. Ventricular septal defect was diagnosed in (4. 1±2. 3)% in the group of the children under examination and this exceeds the general population figures. The combination of cardiac defects with other anomalies was observed in (16.7 ± 8, 8)% of children. CM of the digestive system were mainly represented by small anomalies of development and were diagnosed in (13. 5 ± 3. 9)% of the children. CM of the urinary tract was detected in (5. 4 ± 2.6) % of the examined children. Congenital defects of the musculoskeletal system were detected in (8. 1 ± 3. 2)% of the children. Congenital defects of the CNS were diagnosed in (4, 1±2, 3)% of the children. The influence of various factors on the emergence of defects and anomalies of development was analyzed. CM’s emergence was significantly influenced by mother’s age (χ2 = 4.18, p = 0.04). The association of CMs emergence with anemia during the pregnancy was revealed (χ2= 5, 89, р = 0, 01) also. Conclusions: In ART children congenital defects and malformations anomalies of the cardiovascular, urinary, digestive, musculoskeletal and sensory organs were the most frequent. The incidence of anomalies is associated with a state of somatic and reproductive health of the mother. Key words: assisted reproductive technology, congenital defect and malformation.